Restrictions on Nickel Exports: National Policy vs International Law - Surayya, Dina Pasya (Journal of ASEAN Dynamics and Beyond, 2023)
International trade is a form of economic activity that forms into business activities that will experience continuous growth and development. International trade was first made from mainland Europe, which then spread to mainland Asia and Africa. Indonesia's nickel metal delivery boycott approach has provoked the European Union to take steps to request Indonesia to the WTO. The EU's protests and claims against Indonesia were launched on the grounds that the EU had been highly subordinated to the shipment of Indonesian nickel minerals. This examination was conducted using a quantitative descriptive strategy with a written and expressive audit approach. In the debate between Indonesia and the European Union because it is already in the WTO's grip, the regulation is based on WTO rules. The problem with the nickel trade restrictions imposed by Indonesia in cases of EU complaints to the World Exchange Organization (WTO) is that it is not justifiable to limit EU makers, especially for nickel